Pengaruh Efektivitas Instagram Ads Dan Perceived Value Terhadap Brand Awareness Produk Case Handphone Android Pada Konsumen Generasi Z. - Riki Ardiyanto; Muhammad Aqil Rozan; Ahmad Basyir; Ria Aulia (CV. ITTC INDONESIA, 2026)
This study aims to examine the influence of Instagram Ads effectiveness and perceived value on brand awareness of Android phone case products among Generation Z consumers. The research employed a quantitative approach using a survey method. Data were collected from 91 respondents through a structured questionnaire using a four-point Likert scale. The collected data were analyzed using IBM SPSS Statistics, including descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The findings indicate that the research instruments are valid and reliable, and the regression model satisfies the classical assumptions. The results reveal that Instagram Ads effectiveness has a positive and significant effect on brand awareness. Likewise, perceived value also has a positive and significant effect on brand awareness. Simultaneously, Instagram Ads effectiveness and perceived value significantly influence brand awareness among Generation Z consumers. These findings suggest that businesses should optimize the quality of Instagram advertising while enhancing consumers' perceived value to strengthen product brand awareness.